2006
DOI: 10.1080/17405620500412267
|View full text |Cite
|
Sign up to set email alerts
|

Categorical flexibility in children: Distinguishing response flexibility from conceptual flexibility; the protracted development of taxonomic representations

Abstract: This research explored the development of children's use of multiple conceptual organizations (thematic, taxonomic) in sorting sets of pictures. Experiment 1 revealed that between 5 and 9 years, two forms of categorical flexibility can be distinguished: Response and conceptual flexibility. It appeared that children's multiple sorts do not necessarily reflect the use of different conceptual organizations. Such lag was mainly due to a difficulty of access to taxonomic representations, specifically in the younger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 49 publications
8
54
0
4
Order By: Relevance
“…More precisely, flexible behaviour would be easier to engage in when the task to switch to only necessitates processing perceptual features of stimuli rather than when it requires identifying and interpreting semantic features. Consistent with this, preschoolers scored better on the traditional version of the DCCS (that involves switching between perceptual tasks) than on a version that required switching between semantic tasks (things that go outside/inside and toys/clothes; Bialystok & Martin, 2004; for convergent evidence, see Blaye et al, 2007;Blaye & Jacques, 2009;Blaye et al, 2006). In summary, research in adults has shown that persisting involuntary activation from a previous task set, and priming of that task set from irrelevant stimulus dimensions, can interfere with performance on the currently relevant task.…”
Section: Overcoming the Previously Relevant Taskmentioning
confidence: 80%
See 1 more Smart Citation
“…More precisely, flexible behaviour would be easier to engage in when the task to switch to only necessitates processing perceptual features of stimuli rather than when it requires identifying and interpreting semantic features. Consistent with this, preschoolers scored better on the traditional version of the DCCS (that involves switching between perceptual tasks) than on a version that required switching between semantic tasks (things that go outside/inside and toys/clothes; Bialystok & Martin, 2004; for convergent evidence, see Blaye et al, 2007;Blaye & Jacques, 2009;Blaye et al, 2006). In summary, research in adults has shown that persisting involuntary activation from a previous task set, and priming of that task set from irrelevant stimulus dimensions, can interfere with performance on the currently relevant task.…”
Section: Overcoming the Previously Relevant Taskmentioning
confidence: 80%
“…First, it may be easier to selectively attend to perceptual rather than semantic properties (Bialystok, 1999;Bialystok & Martin, 2004). Indeed, it is easier for school-age children to maintain or switch to thematic rules that can be easily conceptualized than it is to maintain or switch to hard-to-conceptualize taxonomic rules (Blaye, Bernard-Peyron, Paour, & Bonthoux, 2006;Blaye, Chevalier, & Paour, 2007;Blaye & Jacques, 2009;Maintenant & Blaye, 2008). Secondly, with a small set size, specific stimulus -response associations rather than task-level associations may be employed (Kray & Eppinger, 2006;Rogers & Monsell, 1995).…”
Section: Stimulimentioning
confidence: 99%
“…7 In fact, even 4-year-olds seem to have severe problems with flexible switching when strong situational cues are absent. Blaye, Bernard-Peyron, Paour, and Bonthoux (2006) gave children a free sorting task with sets of colored pictures that could be grouped into three different categories. Approximately half (43%) of the 4-year-olds were not able to sort the items according to thematic or taxonomic organizations, and all of the others (except two) were not able to use more than one correct grouping.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the strength of preschoolers' working memory representation of rules determines their rule-switching speed even when they do not make errors (Holt & Deák, 2015). Children's conceptual knowledge also affects how readily they switch between subtasks (Blaye, Bernard-Peyron, Paour, & Bonthoux, 2006;Deák, Ray, & Pick, 2004). Thus, specific knowledge affects flexibility, and it is important to control or assess the specific difficulty of each (cue-or rule-based) subtask, and of each test overall, in order to interpret similarities and differences between tests.…”
Section: Introductionmentioning
confidence: 99%